Cho biểu thức: \(P=\frac{2{{a}^{2}}}{{{a}^{2}}-1}+...

Câu hỏi: Cho biểu thức: \(P=\frac{2{{a}^{2}}}{{{a}^{2}}-1}+\frac{a}{a+1}-\frac{a}{a-1}\)a) Tìm \(a\) để biểu thức \(P\) có nghĩa.b) Rút gọn của \(P\) là:c)  Giá trị nguyên của \(a\) để \(P\) có giá trị nguyên là:

A \(a,\ a\ne \pm 2\)

\(b,\ P = \frac{{2a}}{{a + 1}}\)

\(c,\ a\in \left\{ -3;-2;0 \right\}\)

B \(a,\ a\ne \pm 1\)

\(b,\ P = \frac{{2a}}{{a - 1}}\)

\(c,\ a\in \left\{ -3;-2;0 \right\}\)

C \(a,\ a\ne \pm 1\)

\(b,\ P = \frac{{2a}}{{a + 1}}\)

\(c,\ a\in \left\{ -3;-2;0 \right\}\)

D \(a,\ a\ne \pm 1\)

\(b,\ P = \frac{{2a}}{{a - 1}}\)

\(c,\ a\in \left\{ 3;-2;0 \right\}\)